An Insight in the Beauty of the Fibonacci - Adhikari, Iswar Mani; Kattel, Parameshwari (Journal of Nepal Mathematical Society, 2023)
Mathematics and architecture have strong logical interconnections. Ratios are good examples of their interconnectivity. Without mathematics, it is hard to believe the existence of science and arts. It is not an exaggeration to say that mathematics is everywhere. Nature is beautiful due to the proper ratios of various components in them and in relation to others. The Fibonacci sequence is one of nature’s numbering systems. It is abundant in nature. It has a close relationship with the golden ratio. Golden ratios and such Fibonacci numbers are found to be used in designing logos, magazine covers, plastic surgery, to name a few. These two are two fascinating topics for mathematicians, artists, natural scientists, and philosophers. This work presents a panoramic view of the Fibonacci numbers, and the Fibonacci sequences; their mathematical presentations, patterns, properties, and beauty.